Suppression of Vortex-induced vibration of a circular cylinder with a pair of curved plates. (1st June 2023) - Li, Boyang; Lv, Jingze; Zhang, Baoshou; Li, Canpeng; Lu, Jie
Abstract: A pair of curved plates are installed behind the cylinder to suppress the VIV response of the cylinder. The effects of the distances ( e = 1 D, 2 D, 3 D and 6 D ) between the cylinders and the curved plates and plate lengths ( L = 0.1 D, 0.5 D and 1 D ) on the VIV response are simulated by combining k-ω SST turbulence models and uRANS equations. The accuracy of the numerical simulation is verified by comparison with the experiment data. The results show that when e = 3 D, the curved plate has the best vibration suppression effect on the VIV response. The maximum amplitude ratio is 0.56, which is 42% less than that of the bare cylinder (0.98). When e = 1 D, the curved plates enhance the VIV response. Especially in the lower branch, the amplitude ratio reaches 0.93, which is far greater than that of the bare cylinder. In addition, when U* >10, the cylinder with a pair of curved plates exits the lock-in region. Besides, the vibration suppression effect of plate length on cylinder is further studied. When L = 1 D, the curved plate has the best vibration suppression effect on the cylinder. The maximum amplitude ratio is 0.37, which is 62% less than that of the bare cylinder. Highlights: The suppression effect of a pair of curved plates on the cylinder is studied. The effects of plate distances and plate length on the VIV response are simulated. The amplitude ratio of cylinder with a pair of curved plates is reduced by 62%. The cylinder with a pair of curved plates is easier to exit the lock-in region. The VIV response is simulated and calculated using Fluent software.